(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2014)
Remittances are defined as the money transmitted from one place to another. Although remittances can also be sent in-kind, the term remittances usually refers to cash transfers. Migrant worker remittances are the part of total remittance flows that is transmitted by migrant workers, usually to their families or friends back home. Remittances are an important and stable source of income for households, in particular in developing countries. Analytical studies have shown that the flow of remittances is the least influenced by economic downturn and remains a stable source of income. Remittances have been identified as the third pillar of development as their volume is second to foreign direct investment and higher than overseas development assistance.Under the altruistic view, the migrant sends remittances home because he cares about the well being of his / her family in the home country, and the remittance satisfies the immigrants concern for the welfare of his family. Opposite to the altruistic motive is the immigrant who sends remittances to the home country mainly for economic reasons and financial self-interest. This paper tries to focus on choice between formal and informal channels which depends on a variety of factors, including the efficiency, the level of charges and exchange rates, the availability of facilities for transferring funds, the prevalence of political risks and the degree of flexibility in foreign exchange rules. It also put an insight into the size and frequency of total remittance flows determined by several factors, such as: the number of migrant workers, wage rates, economic activity in the host country/region and in the sending country/region, exchange rates, political risk, facilities for transferring funds, marital status, level of education of the migrant, whether or not accompanied by dependents, years since out migration, household income level, relative interest rate between labour-sending and receiving and peeps into its effect on the BOP of the country.